Friction stir spot welding of aluminum and carbon fiber reinforced thermoplastic using hybrid surface treatment improving interfacial properties. (15th December 2021) - Ota, Eri; Matsuda, Tomoki; Shoji, Hiroto; Ogura, Tomo; Miyasaka, Fumikazu; Sano, Tomokazu; Ohata, Mitsuru; Hirose, Akio
Graphical abstract: Highlights: High-strength Al/CFRTP joint was achieved by FSSW under hybrid treatment of HCl immersion and silanization. Miniature tensile test showed the hybrid treatment improved interfacial strength more than heat-affected CFRTP. Change of the fracture behavior from interfacial to CFRTP fracture led to an increase in cross tension strength. HCl immersion formed dendritic nanostructures generating mechanical interlocking and increased wettability of an Al surface. Al and CFRTP were joined through the O and Si layers at the interface. Abstract: In this study, the synergistic effects of a hybrid surface treatment involving hydrochloric acid (HCl) immersion and silanization on friction stir spot welding (FSSW) of aluminum and carbon fiber reinforced thermoplastic (CFRTP) were investigated. Maximum tensile shear strength of 10.2 kN and maximum cross-tension strength of 1.92 kN were achieved. An unloading test and a miniature tensile test revealed that the fracture behavior changed from interfacial to CFRTP fracture due to increased interfacial strength with the hybrid treatment and utilization of the CFRTP strength enhanced the joint strength. The nanostructures at the interface with HCl immersion treatment indicated that the interfacial properties were improved mechanically in addition to the chemical enhancement by silanization. Owing to the hybrid treatment, aluminum and CFRTP were efficiently joined by the adhesion behavior of spreading melted plastic resin during the FSSW process.